Excitation of high-latitude MAC waves in Earth's core. Issue 3 (2nd February 2023) - Nicolas, Quentin; Buffett, Bruce
SUMMARY: Recent geomagnetic observations reveal localized oscillations in the field's secular acceleration at high latitudes, with periods of about 20 yr. Several types of waves in rotating magnetized fluids have been proposed to explain equatorial oscillations with similar high frequencies. Among these are non-axisymmetric Alfvén waves, magneto-Coriolis waves and, in the presence of fluid stratification, magnetic-Archimedes–Coriolis (MAC) waves. We explore the hypothesis that the observed high latitude patterns are the signature of MAC waves by modelling their generation in Earth's core. We quantitatively assess several generation mechanisms using output from dynamo simulations in a theoretical framework due to Lighthill. While the spatio-temporal structure of the sources from the dynamo simulations are expected to be realistic, their amplitudes are extrapolated to reflect differences between the simulation's parameter space and Earth-like conditions. We estimate full wave spectra spanning monthly to centennial frequencies for three plausible excitation sources: thermal fluctuations, Lorentz force and magnetic induction. When focusing on decadal frequencies, the Lorentz force appears to be most effective in generating high-latitude MAC waves with amplitude estimates falling within an order of magnitude of observed oscillations. Overall, this study puts forward MAC waves as a viable explanation, in the presence of fluid stratification at the top of Earth's core, for observed field variations at high latitudes.